Genetic evidence for functional interaction of the Escherichia coli signal recognition particle receptor with acidic lipids in vivo - Erez, Elinor; Stjepanović, Goran; Zelazny, Adrian M.; Brügger, Britta; Sinning, Irmgard; Bibi, Eitan (The journal of biological chemistry, 2010)
The mechanism underlying the interaction of the Escherichia coli signal recognition particle receptor FtsY with the cytoplasmic membrane has been studied in detail. Recently, we proposed that FtsY requires functional interaction with inner membrane lipids at a late stage of the signal recognition particle pathway. In addition, an essential lipid-binding α-helix was identified in FtsY of various origins. Theoretical considerations and in vitro studies have suggested that it interacts with acidic lipids, but this notion is not yet fully supported by in vivo experimental evidence. Here, we present an unbiased genetic clue, obtained by serendipity, supporting the involvement of acidic lipids. Utilizing a dominant negative mutant of FtsY (termed NG), which is defective in its functional interaction with lipids, we screened for E. coli genes that suppress the negative dominant phenotype. In addition to several unrelated phenotype-suppressor genes, we identified pgsA, which encodes the enzyme phosphatidylglycerophosphate synthase (PgsA). PgsA is an integral membrane protein that catalyzes the committed step to acidic phospholipid synthesis, and we show that its overexpression increases the contents of cardiolipin and phosphatidylglycerol. Remarkably, expression of PgsA also stabilizes NG and restores its biological function. Collectively, our results strongly support the notion that FtsY functionally interacts with acidic lipids.